ANALISIS DAMPAK DIGITALISASI SISTEM KEUANGAN INDONESIA TERHADAP PERMINTAAN UANG KARTAL - Virnanda, Yohana; Suman, Agus (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
The growth of technology that has an impact on the financial world causes people's responses to change so, research about the effect of digitization of the Indonesian financial system on the demand for cash with a research period from 2018 to 2022 using the Autoregressive Distributed Lag (ARDL) method by secondary data is carried out. The results showed that in the short term, the previous period of cash, credit cards, electronic money in 2022 and 2020 also inflation negatively affected the demand for cash. While in the long run, only the transaction value of ATM/Debit cards and credit cards have a negative effect on changes in Y. Increased use of non-cash payment instruments that are able to reduce the composition of cash for daily transactions must be accompanied by improved payment system policies, the legalization of digital rupiah and support for improving public financial literacy.